Access to Adolescent Pregnancy Prevention Information and Services in Ghana: A Community-Based Case-Control Study - Ahinkorah, Bright Opoku; Hagan, John Elvis; Seidu, Abdul-Aziz; Budu, Eugene; Hormenu, Thomas; Mintah, Joseph Kwame; Sambah, Francis; Schack, Thomas (Frontiers in Public Health, 2019)
Background: Pregnancy among girls 10-19 years remains a challenge that requires critical resolution all over the world. Despite this worrying sexual phenomenon, research pertaining to prevention information and related services in Sub-Saharan nations like Ghana is sparse. This study sought to determine the influence of access to pregnancy prevention information and services on adolescent pregnancy in the Komenda-Edina-Eguafo-Abrem Municipality in the Central Region of Ghana. Methods and results: Adopting a matched case-control research design with a 1:1 mapping, female adolescents aged between 15-19 years in the KEEA Municipality were selected using a facility based sampling technique. Results from both bivariate and multivariate analyses revealed that non-pregnant adolescents were about 2 times more likely to have access to pregnancy prevention information from health workers compared to pregnant adolescents (OR = 0.57, 95% CI = [0.33-0.96, p = .036). Likewise, pregnant adolescents were 5 times more likely to have access to pregnancy prevention information from media compared to non-pregnant adolescents (OR = 5.44, 95% CI = [2.64-11.23], p = .000). Additionally, non-pregnant adolescents were 2 times more likely to receive information on pregnancy prevention from school compared to pregnant adolescents (OR = 0.48, 95% CI = [0.28-0.81], p = .006). Conclusion: Sexuality and reproductive health (SRH) programme organizers should target specific intervention programmes that focus on training health workers and/or other analogous staff to enhance their awareness, attitudes, and skills to more effectively meet with the specific needs of adolescents. Specific health workers training and redesign of health facilities to foster more adolescent user friendly working environment (e.g., extension in operational times, reduction in fees of SRH services, transforming physical design to promote privacy or conﬁdentiality) ought to be encouraged. Different media outreach programmes should also combine other community level events (e.g., informative methods through schools [e.g., focus group discussions, participatory learning], assisting connections to health services, community information network [e.g., use of sirens]) to provide well–tailored advocacy that would help modify SRH and sociocultural norms that hinder positive sexual behaviours among young people.